PERSONAL HYGIENE GUARANTEE FOOD OF FOOD HOUSE IN PUSKESMAS PAAL V REGION KOTA BARU IN JAMBI CITY 2019 - Sondang Siahaan; Supriatna; Rina Fauziah; Suparmi (Universitas Adiwangsa Jambi, 2022)
Personal hygiene is a personal hyiene effort that is carried out tomaintain health and enhance the level of his own health. The purpose ofthis study was to determine the habit of bathing, the habit of cleaningteeth, the habit of cleaning the nose, the habit of cutting nails and washinghands, the habit of wearing headgear, the habit of wearing mouth masks,and the health check.This research method is descriptive in nature to describe theapplication of personal hygiene of food handlers of restaurants in the workarea of Puskesmas Paal V in 2019. Data taken from observations of foodhandlers using a checklist of the total sample of this study were 37respondents.The results showed that personal hygiene food handlers with goodbathing habits 97.29%, good teeth cleaning habits 13.51%, good nosecleaning habits 21.62%, good nail cutting habits and hand washing habits45.95%, habit of using cover head 48.65%. The habit of using mouthmasks as well as health checks does not exist.The conclusion in this study is that there are still many food handlerswho are not aware of personal hygiene.